UTICAJ TURISTIČKOG MENADŽMENTA NA UPRAVLJANJE TURISTIČKIM PREDUZEĆIMA NA RAZLIČITIM TERITORIJALNIM NIVOIMA - Petkova, Elena (International Journal of Economic Practice and Policy, 2025)
Tourism enterprise management is part of tourism management. The successful management of the tourism enterprise that is performed by its managers depends on considering the trends and patterns of tourism management at the different territorial levels - global, supranational, national, regional, and local. That is why the managers of the tourism enterprise must know and comply with the managerial decisions, which are taken in the field of tourism at the different territorial levels. Management decisions in the field of tourism at the global, supranational, national, regional, and local levels have an impact on the functioning and management of the individual tourism enterprise. The paper examines the place of tourism enterprise management in the tourism management system at the different territorial levels. In this direction, important examples of how tourism management at different territorial levels (global, national, supranational, regional, and local) affects the management of the individual tourism enterprise are presented and analyzed. Particular attention is paid on the influence of tourism management in Bulgaria at the national, regional, and local levels on the management of tourism enterprises. As a result of the analysis, it can be concluded that with a view to achieving success tourism enterprise managers should consider the impact of tourism management at different territorial levels on tourism enterprises when developing plans and programs and making decisions as regards to both, general management and financial, marketing and personnel management.
Keywords: tourism; management; teritorial level; tourism entreprises; Bulgaria